KEDUDUKAN DAN PARTISIPASI LEMBAGA ADAT DALAM PEMBENTUKAN PERATURAN PEKON DI PEKON WAY EMPULAU ULU KEC. BALIK BUKIT, KAB. LAMPUNG BARAT - msk, indah maulidiyah; yusdiyanto, yusdiyanto; saleh, ahmad (Lampung University, 2014)
This research aims to ascertain the position of Customary Institution in forming the Village Regulation, and also its role in the Way Empulau Ulu, Subdistrict - Balik Bukit, West Lampung. This research uses the method of normative-empirical; by doing library research, field research, and interviews. Results of the discussion showed that the Customary Institution of Way Empulau Ulu has the same position with the Institution of Rural Association. Although the Customary Institution has a position that is outside of organizational structure within the Village government, but the role of Customary Institution in forming the Village Regulation is just the structural and position of Customary Institution functionally is still less than optimal in the communication and interaction between the village government and the villagers.Â Keywords: Position of Customary Institution, Participation of Customary Institution